2021
DOI: 10.3390/biom11030403
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Hub Genes and Key Pathways Associated with Anti-VEGF Resistant Glioblastoma Using Gene Expression Data Analysis

Abstract: Anti-VEGF therapy is considered to be a useful therapeutic approach in many tumors, but the low efficacy and drug resistance limit its therapeutic potential and promote tumor growth through alternative mechanisms. We reanalyzed the gene expression data of xenografts of tumors of bevacizumab-resistant glioblastoma multiforme (GBM) patients, using bioinformatics tools, to understand the molecular mechanisms of this resistance. An analysis of the gene set data from three generations of xenografts, identified as 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 76 publications
(81 reference statements)
1
8
0
Order By: Relevance
“…Arya et al have shown that by analysing the gene expression data of xenografts of tumours of glioblastoma patients, the resistance mechanism involved PI3K-Akt, cell cycle, and other related signalling pathways. 6 We obtained similar results using real in vivo genomic data in TISF, suggesting this could be a potential mechanism of treatment and resistance associated with bevacizumab treatment.…”
Section: F I G U R Esupporting
confidence: 64%
“…Arya et al have shown that by analysing the gene expression data of xenografts of tumours of glioblastoma patients, the resistance mechanism involved PI3K-Akt, cell cycle, and other related signalling pathways. 6 We obtained similar results using real in vivo genomic data in TISF, suggesting this could be a potential mechanism of treatment and resistance associated with bevacizumab treatment.…”
Section: F I G U R Esupporting
confidence: 64%
“…3b). Some were (i) shown to be part of prognostic markers (SLC12A4-CHEK2 (77)), (ii) differentially expressed together in response to perturbations (SEMA3C-TCEAL1 (78), IGFBP2-SIX1 (79), TINCR-POU2AF1 (80), NTSR1-TOMM6 (81)), and (iii) part of gene signatures for different classes of tumors (SNORA73A-MAPK (82), FDCSP-GJA1 (83)). A few of the associations had related mechanistic interactions as well (CDC42-MTOR (84,85), IGFBP2-SIX1 (79), WTAP-STAT3 (86,87), TINCR-POU2AF1 (80)).…”
Section: Resultsmentioning
confidence: 99%
“…A study by Zhu et al (2020) demonstrated that AKT suppression could disrupt VM formation and angiogenesis in glioma orthotopic xenografts and glioma cells (Zhu et al, 2020). Kesavan et al (2021) used pathway enrichment analysis to show that 16 genes in the Akt pathway were upregulated, suggesting the pathway is activated in GBM and possibly responsible for the formation of resistance to anti‐VEGF therapy in GBM (Arya et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…(2021) used pathway enrichment analysis to show that 16 genes in the Akt pathway were upregulated, suggesting the pathway is activated in GBM and possibly responsible for the formation of resistance to anti-VEGF therapy in GBM (Arya et al, 2021).…”
Section: F I G U R Ementioning
confidence: 99%